2023
DOI: 10.1021/acsaem.2c03543
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Porous Carbon-Supported PtCo Nanoparticle Electrocatalyst for Oxygen Reduction Reaction Prepared by a Dual-Template Method

Abstract: A strategy for preparing nitrogen-doped porous carbon (NPC-Co) using a dual-template method is reported in this study. The catalyst (PtCo/NPC-Co) with high catalytic performance for the oxygen reduction reaction (ORR) was developed after adding PtCo metal nanoparticles (NPs). Polydopamine can complex metals, encapsulate templates, and reduce metals. Therefore, polydopamine was selected as the carbon and nitrogen source. Then, ZnO and Co NPs were used as a double template to obtain a carrier (NPC-Co) with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…17 However, these performance issues may be related to the fact that graphitized carbon tends to have fewer defect sites that bind to the catalyst material, resulting in poor dispersion and diminished performance. 23 Furthermore, graphitized carbon supports have lower Brunauer-Emmett-Teller (BET) surface areas. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 However, these performance issues may be related to the fact that graphitized carbon tends to have fewer defect sites that bind to the catalyst material, resulting in poor dispersion and diminished performance. 23 Furthermore, graphitized carbon supports have lower Brunauer-Emmett-Teller (BET) surface areas. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 Another concern with using Pt as a catalyst is the agglomeration of PtNPs, which leads to a reduction of electrocatalytic activity 5 and corrosion of the carbon support, 6 both of which can be minimized through the optimization of the support material. 7 The support onto which the PtNPs are attached influences the overall electrocatalytic activity of the electrocatalyst. The metal−support interaction has an influence on the metal's electronic properties and therefore the metal's charge-transfer properties.…”
Section: Introductionmentioning
confidence: 99%
“…This dependence on size confirms the Pt particle size effect on the ORR . Another concern with using Pt as a catalyst is the agglomeration of PtNPs, which leads to a reduction of electrocatalytic activity and corrosion of the carbon support, both of which can be minimized through the optimization of the support material …”
Section: Introductionmentioning
confidence: 99%
“…11 Another is the strain effect: nonmetallic atomic doping can alter the interatomic distance on the catalyst surface to optimize oxygen reduction catalysis. 12,13 It has been reported that the lone electron pair in nitrogen (N) can facilitate O-O bond cleavage and enhance electrocatalytic activity. 14 Apart from electronic structure modulation, another typical method of elevating catalytic activity is the adjustment of the electrocatalyst morphological structure to maximize the number of active sites.…”
mentioning
confidence: 99%